Relevance of the Aboriginal Rethink Sugary Drink media campaign to Aboriginal and non‐Aboriginal audiences in regional Victoria - Jennifer Browne; Catherine MacDonald; Mikaela Egan; Kylie Carville; Robyn Delbridge; Kathryn Backholer (Australian and New Zealand Journal of Public Health, 2021)
Abstract Objective: To test the hypothesis that a culturally tailored sugar‐sweetened beverage (SSB) campaign designed specifically for the Victorian Aboriginal community will not only be valuable for Aboriginal Victorians but will also have cross‐over benefits for non‐Aboriginal Victorians. Methods: An online survey was completed by 155 Victorians (78 Aboriginal, 77 non‐Aboriginal) four months after the Aboriginal Rethink Sugary Drink (RSD) advertisement was launched. Differences between Aboriginal and non‐Aboriginal respondents were assessed using χ2 and Wilcoxon rank‐sum tests. Results: Seventy‐six per cent of Aboriginal respondents recalled seeing the advertisement compared to 56% of non‐Aboriginal respondents (p<0.05). A high proportion of respondents (59% for Aboriginal, 55% for non‐Aboriginal) who had seen the advertisement correctly identified the sugar content of a 600mL drink. The perceived relevance of the advertisement was high (78% for Aboriginal vs. 47% for non‐Aboriginal; p=0.003), as was the response that it motivated action to improve health (82% vs. 50%; p=0.001). Conclusion: Notwithstanding the small sample size, the Aboriginal advertisement appeared to engage both Aboriginal and non‐Aboriginal Victorians and promote SSB knowledge and motivation to improve health, particularly among Aboriginal Victorians, who were the target population. Public health campaigns should be designed with Aboriginal Australians to ensure equitable reach and impacts across the whole population. Implications for public health: Aboriginal‐led health promotion campaigns may be beneficial for both Aboriginal and non‐Aboriginal audiences.